A novel silane system as a primer for orthodontic bonding—A pilot study. (October 2015) - Durgesh, Bangalore H.; Hijji, Saleh Al; Kheraif, Abdulaziz A Al; Ramakrishnaiah, Ravikumar; Basavarajappa, Santhosh; Al Sharawy, Mohammed; Pekka Matinlinna, Jukka
Abstract: Aim: To determine the adhesion strength (measured as shear bond strength, SBS) of orthodontic brackets using two experimental silane-based primer systems and compare and contrast their effect. Materials and methods: Sixty acid-etched premolars were randomly assigned into 4 study groups ( n =15). In group 1, brackets were bonded without primer but using Transbond XT adhesive; in group 2, Transbond XT primer was applied and bracket bonded; in group 3, an experimental silane-based primer of 1.0 vol% of 3-acryloxypropyltrimethoxysilane (ACPS) was applied before bonding; in group 4, an experimental silane-based primer of 1.0 vol% of ACPS+0.5% bis -1, 2-(triethoxysilyl) ethane (BTSE) was used. The adhesion strength (measured as shear bond strength) was recorded using a universal testing machine. Failure types were classified according to the Adhesive Remnant Index (ARI). Contact angles of the primers were measured on an enamel slab. Data was analyzed by ANOVA and Tukey's multiple comparison post hoc analysis. Results: The mean adhesion strength results were high in group 4: 15.8±1.6 MPa followed by group 3: 12.5±1.5 MPa, group 2: 11.9±1.1 MPa and the lowest in group 1: 08.1±0.7 MPa. A significant difference in adhesion strength was observed between all the groups except for group 3 and group 4 ( p <0.01). The ARI score was distributed largely to 0 and 1. One instance of enamel fractures was recorded in group 1. The contact angle measurements suggested that the lowest value with the experimental primer containing (ACPS+BTSE) was, <5° followed by Transbond XT, 41.86±4.56°. Conclusion: The experimental silane primer systems were hydrophilic in nature and demonstrated higher adhesion strength compared to traditional orthodontic primers.